2021
DOI: 10.17533/udea.ikala.v26n2a06
|View full text |Cite
|
Sign up to set email alerts
|

Violencia simbólica contra la mujer en los anuncios publicitarios: un análisis visual crítico

Abstract: El discurso publicitario es conocido por contribuir al sexismo y a la reproduc­ción de estereotipos de género. Este artículo se centra en la violencia simbólica que presenta el cuerpo de las mujeres como objeto sexual en textos publicitarios empleados por Dolce & Gabbana en la hoja informativa (newsletter) que envió, a través de la web, regularmente entre 2016 y 2019. La metodología utilizada fue fundamentalmente cualitativa, aunque se tuvieron en cuenta algunos datos cuan­titativos para comprender mejor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Classic illustrated books have also proved to be beneficial in raising gender awareness, as outdated or anachronistic representations of social values such as gender values are salient for the modern reader's eye, and therefore are efficient ways of exploiting intuitive approaches to gender bias identification [15]. Other multimodal artefacts, such as advertisements, have also proven to be useful for discussing gender (in)equalities, as authors such as Martínez Lirola [16] have shown, and for this reason their applicability is also considered for the aims of the project.…”
Section: Theoretical Framework Appliedmentioning
confidence: 99%
See 1 more Smart Citation
“…Classic illustrated books have also proved to be beneficial in raising gender awareness, as outdated or anachronistic representations of social values such as gender values are salient for the modern reader's eye, and therefore are efficient ways of exploiting intuitive approaches to gender bias identification [15]. Other multimodal artefacts, such as advertisements, have also proven to be useful for discussing gender (in)equalities, as authors such as Martínez Lirola [16] have shown, and for this reason their applicability is also considered for the aims of the project.…”
Section: Theoretical Framework Appliedmentioning
confidence: 99%
“…Step 2: Describing systematically multimodal artefacts by means of Visual Social Grammar (Kress & Van Leeuwen 2001, 2006, 2021: In this phase, the set of multimodal artefacts is discussed and categorised according to their perceived descriptive features (e.g gender and professions, gender and physical appearance, gender and agency, etc.). The previous (superficial) descriptions are now linked to the analytical models by Halliday and Kress and van Leeuwen, so that the representation of gender in each multimodal artefact is described by linking what we see (and read) in each text in relation to the three dimensions described below.…”
Section: )mentioning
confidence: 99%